Preparation method of aluminum hydroxide

By controlling the caustic ratio of sodium aluminate solution, adding stabilizers and using seed crystals that induce decomposition activity, combined with washing, drying and crushing steps, the problems of high sodium mass fraction and coarse grains in traditional aluminum hydroxide preparation are solved, and the preparation of high-performance aluminum hydroxide is achieved.

CN120817620APending Publication Date: 2025-10-21CHALCO SHANDONG NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510915526.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-03
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

Traditional aluminum hydroxide preparation methods have problems such as high sodium mass fraction, insufficient whiteness and coarse grains, which make it difficult to meet the requirements of high-end applications, especially the ultra-low sodium requirements in boehmite precursors for lithium battery separators.

Method used

The preparation process of aluminum hydroxide is optimized by controlling the caustic ratio of sodium aluminate solution in the range of 1.30 to 1.70, adding stabilizers and using seeds with induced decomposition activity, combined with multi-stage countercurrent washing, drying and crushing steps.

Benefits of technology

The deep removal of the mass fraction of sodium in aluminum hydroxide is achieved, the whiteness is increased to more than 98%, and the particle size D50 is 1.0 to 3.0 μm, meeting the performance requirements of high-end applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120817620A_ABST
    Figure CN120817620A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of aluminum hydroxide, which comprises the following steps: dissolving an aluminum source material in alkali liquor to form a sodium aluminate solution; the caustic ratio of the sodium aluminate solution is 1.30 to 1.70; adding a stabilizer into the sodium aluminate solution; enabling the sodium aluminate solution containing the stabilizer to be in contact with a seed crystal with induced decomposition activity, and carrying out decomposition reaction to obtain a decomposition product; and sequentially washing, drying and crushing the decomposition product to obtain an aluminum hydroxide product. According to the embodiment of the invention, through the steps of controlling the caustic ratio of the sodium aluminate solution, adding the stabilizer, using the seed crystal with induced decomposition activity and optimizing post-treatment, adsorption and wrapping of sodium ions in the aluminum hydroxide are reduced through the synergistic effect of a plurality of links, so that deep removal of the mass fraction of sodium in the aluminum hydroxide is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of inorganic non-metallic materials, and in particular to a method for preparing aluminum hydroxide. Background Art

[0002] Aluminum hydroxide, an important inorganic non-metallic material, is widely used in polymer composite fillers, electronic ceramics, lithium battery separators, and other fields. However, traditional aluminum hydroxide preparation methods have many technical bottlenecks and are unable to meet the stringent performance requirements of high-end applications.

[0003] The traditional process usually adopts the re-dissolution method to prepare aluminum hydroxide, but this method has the following major problems: First, the mass fraction of the prepared sodium aluminum hydroxide is high (Na2O>0.15%), the whiteness is insufficient (<90%), and the grains are coarse (D50>5μm), which cannot meet the ultra-low sodium requirements of boehmite precursors for lithium battery separators (Na2O<0.1%). Secondly, the sodium aluminate solution is prone to heterogeneous nucleation during the decomposition process, resulting in sodium ions being coated inside the crystal lattice, which is difficult to remove by conventional washing. In addition, the existing seed crystals are not active enough and need to be added in excess (>20wt%) or the decomposition time is extended (>20h), resulting in high energy consumption and uncontrollable product particle size. Summary of the Invention

[0004] The present application provides a method for preparing aluminum hydroxide to solve the following technical problem: how to achieve deep removal of sodium from aluminum hydroxide.

[0005] The present invention provides a method for preparing aluminum hydroxide, comprising:

[0006] dissolving an aluminum source material and an alkali solution to form a sodium aluminate solution; wherein the caustic ratio of the sodium aluminate solution is 1.30 to 1.70;

[0007] adding a stabilizer to the sodium aluminate solution;

[0008] contacting the sodium aluminate solution containing a stabilizer with seed crystals having decomposition-inducing activity to carry out a decomposition reaction to obtain a decomposition product;

[0009] The decomposition product is washed, dried and crushed in sequence to obtain an aluminum hydroxide product.

[0010] Optionally, the aluminum source material includes at least one of the following: aluminum hydroxide, aluminum oxide or a hydrate thereof.

[0011] Optionally, the alkali solution includes at least one of the following: sodium hydroxide solution, potassium hydroxide solution, and the purity of the alkali solution is ≥98%.

[0012] Optionally, the caustic ratio of the sodium aluminate solution is 1.40 to 1.60.

[0013] Optionally, the stabilizer includes at least one of the following: an organic phosphoric acid compound, a polycarboxylic acid compound, and an inorganic salt compound, and the mass of the stabilizer is 0.05 to 0.15% of the mass of the sodium aluminate solution.

[0014] Optionally, the specific surface area of ​​the seed crystal is not less than 10m 2 / g, and the sodium mass fraction of the seed crystal is not higher than 0.2%.

[0015] Optionally, the parameters of the decomposition reaction include: a temperature of 50 to 90° C., a time of 10 to 24 hours, and a decomposition rate of the sodium aluminate solution of not less than 30%.

[0016] Optionally, the washing adopts a multi-stage countercurrent washing process, the conductivity of the washing liquid is not higher than 10 μS / cm, and the solid-liquid ratio of the washing is 1:5 to 1:10.

[0017] Optionally, the drying temperature is 60-100° C., and the moisture content of the decomposition product after drying is not higher than 0.5%.

[0018] Optionally, the properties of the aluminum hydroxide product include at least one of the following: sodium mass fraction not higher than 0.05%, whiteness ≥ 98%, and particle size D50 of 1.0 to 3.0 μm.

[0019] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0020] The present application provides a method for preparing aluminum hydroxide. First, the caustic ratio of the sodium aluminate solution (i.e., the molar ratio of caustic soda to aluminum oxide in the solution) has a significant impact on its decomposition process and the properties of the product. When the caustic ratio is between 1.30 and 1.70, the solution is in a relatively stable decomposition range. Within this caustic ratio range, the decomposition reaction of the sodium aluminate solution can proceed more efficiently, while avoiding excessive residual sodium impurities caused by an excessively high caustic ratio. A lower caustic ratio helps reduce the adsorption and encapsulation of sodium ions in the decomposition products, thereby reducing the sodium mass fraction in the aluminum hydroxide. Secondly, the role of the stabilizer is to adjust the chemical environment of the solution, inhibiting the precipitation of impurities and the adsorption of sodium ions. After adding the stabilizer to the sodium aluminate solution, the stabilizer can interact with the sodium ions or other impurity ions in the solution to form stable complexes or change the surface properties of the solution. This can reduce the adsorption of sodium ions on the aluminum hydroxide surface and inhibit the co-precipitation of sodium impurities with the aluminum hydroxide during the decomposition process, thereby reducing the sodium mass fraction in the final product. Third, the seed crystal plays a role in inducing crystallization during the decomposition process of the sodium aluminate solution. The activity and surface properties of the seed crystals will affect the crystallization process and impurity adsorption of the decomposition products. Seed crystals with induced decomposition activity can guide the aluminate ions in the sodium aluminate solution to crystallize and precipitate preferentially on the surface of the seed crystals to form aluminum hydroxide crystals. Because the surface properties of the seed crystals are relatively regular and optimized, they can reduce the adsorption of impurities (including sodium ions) on the crystal surface and promote the growth of purer aluminum hydroxide crystals. This induced crystallization process can effectively reduce the sodium mass fraction in the aluminum hydroxide product. Washing, drying and crushing are post-processing processes for further removing impurities and optimizing product performance. In summary, the embodiments of the present application, by controlling the caustic ratio of the sodium aluminate solution, adding a stabilizer, using seed crystals with induced decomposition activity and optimizing the post-processing steps, work synergistically from multiple links to reduce the adsorption and encapsulation of sodium ions in aluminum hydroxide, thereby achieving a deep removal of the sodium mass fraction in aluminum hydroxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the following summarizes the drawings necessary for the embodiments or the description of the prior art. Obviously, for professionals in this field, other relevant drawings can be derived based on these drawings without creative efforts.

[0023] Figure 1 This is a flow chart of a method for preparing aluminum hydroxide provided in an embodiment of the present application. DETAILED DESCRIPTION

[0024] To more clearly illustrate the purpose, technical solutions, and advantages of the embodiments of the present application, the technical solutions of the embodiments are described in detail below with reference to the accompanying drawings. Please note that the embodiments described herein are merely illustrative and do not represent all possible implementation paths. All other embodiments obtained by persons of ordinary skill in the art based on the embodiments of the present application without creative effort are within the scope of protection of this application.

[0025] The ranges described herein, regardless of numerical values ​​or ratios, include all subranges and individual numerical values ​​therein. For example, when referring to '1 to 6' or '1-6', it means including any subrange from 1 to 6 (such as 1 to 3, 2 to 5) and all individual numbers (1, 2, 3, 4, 5, 6). Unless otherwise specified, the terms "include", "comprising", etc. used herein mean "including but not limited to"; relational terms such as "first" and "second" are only used to distinguish different entities or operations and do not imply an actual sequence or association relationship; "and / or" means that multiple situations can exist alone or simultaneously; expressions such as "at least one", "multiple", and "at least one" all refer to any combination of corresponding objects, including a combination of single or multiple objects. The proportional relationships involved in the text, such as mass ratios, molar ratios, etc., should be understood as the corresponding relationship between the first and second terms of the proportional formula in the order of description. The raw materials, reagents, instruments, and equipment used in this article can all be purchased on the market or prepared by existing methods.

[0026] Figure 1 This is a flow chart of a method for preparing aluminum hydroxide provided in an embodiment of the present application.

[0027] See Figure 1 , the present application embodiment provides a method for preparing aluminum hydroxide, comprising:

[0028] S1. Dissolving an aluminum source material and an alkali solution to form a sodium aluminate solution; wherein the caustic ratio of the sodium aluminate solution is 1.30 to 1.70;

[0029] S2, adding a stabilizer to the sodium aluminate solution;

[0030] S3, contacting the sodium aluminate solution containing the stabilizer with seed crystals having decomposition-inducing activity to perform a decomposition reaction to obtain a decomposition product;

[0031] S4. Washing, drying and crushing the decomposition product in sequence to obtain an aluminum hydroxide product.

[0032] Aluminum source material: refers to aluminum-containing compounds that can be used to prepare sodium aluminate solution, such as aluminum hydroxide, aluminum oxide or its hydrate. Caustic ratio (αk): the molar ratio of sodium hydroxide to aluminum oxide in the sodium aluminate solution, which is an important parameter for measuring the properties of the solution. Stabilizer: an additive used to maintain the stability of the sodium aluminate solution during the decomposition process to prevent the solution from spontaneous hydrolysis or decomposition. Seed crystals that induce decomposition activity: tiny particles with specific physical and chemical properties that can induce the decomposition of the sodium aluminate solution and control the product formation process. Seed crystals include: active seeds prepared by induction with sodium bicarbonate, aluminum hydroxide as a seed crystal for induced decomposition crystallization reactions, metal-organic framework (MOF) seeds, disk-cluster L-type zeolite crystals and seeds for heterogeneous seed-induced crystallization, ZSM-5 catalysts synthesized by the CTAB-assisted seed method, etc.

[0033] An aluminum source material is dissolved in an alkaline solution to form a sodium aluminate solution, and its caustic ratio (αk) is controlled to between 1.30 and 1.70. This caustic ratio is controlled based on the relationship between the decomposition performance of the sodium aluminate solution and αk. When αk is within this range, the solution exhibits suitable reactivity and stability during the subsequent decomposition process, facilitating a smooth decomposition reaction while avoiding issues such as incomplete decomposition or poor solution stability caused by excessively high or low αk. A stabilizer is added to the sodium aluminate solution to further maintain its stability during the decomposition process. The stabilizer prevents spontaneous hydrolysis or decomposition during the decomposition process, ensuring that the decomposition reaction proceeds along the intended path and improving product quality and yield. Seed crystals with decomposition-inducing activity are prepared, and the sodium aluminate solution containing the stabilizer is contacted with the seed crystals to initiate the decomposition reaction. The introduction of the seed crystals is based on their regulatory effect on the decomposition process of the sodium aluminate solution. The seed crystals can induce the aluminate ions in the solution to decompose in a specific manner, thereby controlling the product's physical properties, such as particle size and morphology, and improving its performance. The decomposition product is sequentially washed, dried, and pulverized to obtain aluminum hydroxide. The washing step removes impurities such as residual sodium ions from the decomposition product, reducing the sodium content. The drying and pulverization steps transform the product into a suitable form for application, improving its performance. The caustic ratio (αk) can be 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, 1.60, 1.65, 1.70, and so on.

[0034] In some embodiments, the aluminum source material includes at least one of the following: aluminum hydroxide, aluminum oxide, or hydrates thereof.

[0035] These technical solutions further specify the specific types of aluminum source materials, including one or more of aluminum hydroxide, aluminum oxide, or their hydrates. This limitation is based on the feasibility and effectiveness of different aluminum source materials in forming sodium aluminate solutions during the dissolution process. Aluminum hydroxide and aluminum oxide are common aluminum source materials that effectively dissolve and form sodium aluminate solutions when reacting with alkaline solutions. By selecting the appropriate aluminum source material, the efficiency of the dissolution process and the properties of the solution can be optimized, thereby providing a better foundation for the subsequent decomposition reaction.

[0036] In some embodiments, the alkali solution includes at least one of the following: sodium hydroxide solution and potassium hydroxide solution, and the purity of the alkali solution is ≥98%.

[0037] Purity refers to the proportion of the target component in the substance. These embodiments specify the specific types of alkali solution, including sodium hydroxide solution, potassium hydroxide solution or a combination thereof, and the purity of the alkali solution is ≥98%. The purpose of selecting high-purity alkali solution is to ensure that the aluminum source material can be fully dissolved during the dissolution process to form a pure sodium aluminate solution. Different types of alkali solutions have different reaction characteristics and dissolving abilities when dissolving aluminum source materials. Sodium hydroxide and potassium hydroxide are commonly used alkali solutions that can react with aluminum source materials to form sodium aluminate solutions. By limiting the type and purity of the alkali solution, the quality of the dissolution process and the properties of the solution can be guaranteed, creating favorable conditions for subsequent decomposition reactions. The purity can be: 98%, 98.5%, 99%, 99.5%, 100%.

[0038] In some embodiments, the sodium aluminate solution has a caustic ratio of 1.40 to 1.60.

[0039] In these technical solutions, the caustic ratio (αk) of the sodium aluminate solution is further limited to 1.40 to 1.60. This range is based on a more in-depth study of the relationship between the decomposition performance of the sodium aluminate solution and the caustic ratio. When αk is between 1.40 and 1.60, the solution exhibits better reactivity and stability during the decomposition process. Compared with the wider αk range in claim 1, this narrower range can more accurately control the progress of the decomposition reaction and further improve the quality and performance of the product. For example, within this range, indicators such as the rate of the decomposition reaction and the particle size distribution of the product may be more ideal, thereby better meeting the requirements of high-end applications for aluminum hydroxide products. The caustic ratio (αk) can be: 1.40, 1.42, 1.44, 1.46, 1.48, 1.50, 1.52, 1.54, 1.56, 1.58, 1.60, etc.

[0040] In some embodiments, the stabilizer includes at least one of the following: an organic phosphoric acid compound, a polycarboxylic acid compound, and an inorganic salt compound. The mass of the stabilizer is 0.05 to 0.15% of the mass of the sodium aluminate solution.

[0041] Organophosphate compounds: A class of organic compounds containing phosphate groups, they exhibit excellent chelating properties and can be used to stabilize sodium aluminate solutions. Polycarboxylic acid compounds: Organic compounds containing multiple carboxyl groups, which exhibit a certain chelating ability and can be used to maintain solution stability. Inorganic salt compounds: These are salt compounds that do not contain carbon-hydrogen bonds. Certain inorganic salts can stabilize sodium aluminate solutions through ionic interactions.

[0042] In these technical solutions, the types and mass proportions of stabilizers are limited. The selection of stabilizers is based on their regulatory effect on the stability of the sodium aluminate solution. Organic phosphoric acid compounds, polycarboxylic acid compounds and inorganic salt compounds all have a certain stabilizing effect and can inhibit the spontaneous hydrolysis or decomposition of the solution by complexing or ionic interaction with ions in the solution. The mass proportion of the stabilizer is 0.05% to 0.15% of the mass of the sodium aluminate solution. This range is based on the concentration required for the stabilizer to play an effective role in the solution. Too low a mass proportion may not achieve the expected stabilization effect, while too high a mass proportion may introduce other impurities or affect other properties of the solution. By limiting the types and mass proportions of stabilizers, the stability of the sodium aluminate solution during the decomposition process can be ensured, thereby improving the quality and yield of the product. The mass proportion of the stabilizer can be: 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, etc.

[0043] In some embodiments, the specific surface area of ​​the seed crystal is not less than 10m 2 / g, and the sodium mass fraction of the seed crystal is not higher than 0.2%.

[0044] In these technical solutions, the specific surface area of ​​the seed crystal is limited to not less than 10m 2 / g, and the sodium mass fraction of the seed crystal is not higher than 0.2%. The specific surface area of ​​the seed crystal is an important indicator to measure its induced decomposition activity. A larger specific surface area means that the seed crystal has more active sites and can more effectively induce the decomposition of the sodium aluminate solution, thereby controlling the particle size and morphology of the product. At the same time, limiting the sodium mass fraction of the seed crystal is to avoid the seed crystal itself introducing too much sodium impurities, affecting the purity of the final product. By selecting a suitable seed crystal preparation method, seed crystals that meet the above requirements can be prepared, thereby achieving precise control of the product in the decomposition reaction and improving the performance of the product. The specific surface area can be: 10m 2 / g、11m 2 / g、12m 2 / g、13m 2 / g、14m 2 / g、15m 2 / g、16m2 / g、17m 2 / g、18m 2 / g、19m 2 / g, 20m 2 / g, etc.; the mass fraction of sodium (Na2O) can be: 0%, 0.05%, 0.10%, 0.15%, 0.20%, etc.

[0045] In some embodiments, the parameters of the decomposition reaction include: a temperature of 50 to 90° C., a time of 10 to 24 hours, and a decomposition rate of the sodium aluminate solution of not less than 30%.

[0046] The decomposition rate refers to the percentage of reactants that decompose to form the target product.

[0047] In these technical solutions, the parameters of the decomposition reaction are specified in detail, including a temperature of 50-90°C, a reaction time of 10-24 hours, and a decomposition rate of the sodium aluminate solution of not less than 30%. The temperature and time of the decomposition reaction are important factors affecting the decomposition process. The appropriate temperature can provide sufficient energy to promote the decomposition reaction of the sodium aluminate solution, while time control ensures that the reaction proceeds fully. The decomposition rate is an indicator of the degree of decomposition reaction. A higher decomposition rate means that more sodium aluminate solution is converted into the target product. By limiting the temperature, time, and decomposition rate of the decomposition reaction, the decomposition process can be optimized and the yield and quality of the product can be improved. For example, within this temperature and time range, indicators such as the decomposition reaction rate and the particle size distribution of the product may be more ideal, thereby better meeting application requirements. The temperature can be: 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, etc.; the time can be: 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, etc.; the decomposition rate can be: 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, etc.

[0048] In some embodiments, the washing adopts a multi-stage countercurrent washing process, the conductivity of the washing liquid is not higher than 10 μS / cm, and the solid-liquid ratio of the washing is 1:5 to 1:10.

[0049] Multi-stage countercurrent washing process: A highly efficient washing method that uses multi-stage countercurrent flow to ensure full contact between the washing liquid and solid particles, improving washing efficiency and reducing impurity content. The solid-to-liquid ratio refers to the volume ratio between the solid decomposition products and the washing liquid.

[0050] These technical solutions specify that the washing step utilize a multi-stage countercurrent washing process, with the conductivity of the washing liquid no higher than 10 μS / cm and a solid-to-liquid ratio of 1:5 to 1:10. The multi-stage countercurrent washing process is a highly efficient washing method that ensures full contact between the washing liquid and the solid particles, improving washing efficiency and reducing impurity content. The conductivity of the washing liquid is an important indicator of its purity. Lower conductivity indicates a lower content of impurity ions in the washing liquid, enabling more effective removal of impurities such as sodium ions from the decomposition products. Controlling the solid-to-liquid ratio ensures sufficient contact between the washing liquid and the solid particles during the washing process, thereby achieving better washing results. By defining the specific parameters of the washing process, it is possible to ensure that impurities such as sodium ions in the decomposition products are fully removed, reducing the sodium content of the product and improving its purity. The electrical conductivity can be: 0μS / cm, 1μS / cm, 2μS / cm, 3μS / cm, 4μS / cm, 5μS / cm, 6μS / cm, 7μS / cm, 8μS / cm, 9μS / cm, 10μS / cm, etc.; the solid-liquid ratio can be: 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc.

[0051] In some embodiments, the drying temperature is 60-100° C., and the moisture content of the decomposition product after drying is no more than 0.5%.

[0052] Moisture content refers to the mass fraction of water in a substance.

[0053] In these technical solutions, the drying temperature is limited to 60-100°C, and the moisture content of the dried decomposition product is no more than 0.5%. The purpose of the drying step is to remove moisture from the washed decomposition product, reducing it to a moisture content suitable for the application. An appropriate drying temperature ensures rapid evaporation of moisture while preventing excessively high temperatures from adversely affecting product performance. Controlling the moisture content ensures product stability and performance. A low moisture content means the product is less susceptible to moisture during storage and use, maintaining excellent performance. By limiting the drying temperature and moisture content, the drying process can be optimized, improving product quality and stability. Drying temperatures can include: 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, etc.; moisture contents can include: 0%, 0.05%, 0.10%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45%, and 0.50%.

[0054] In some embodiments, the properties of the aluminum hydroxide product include at least one of the following: a sodium mass fraction not higher than 0.05%, a whiteness ≥ 98%, and a particle size D50 of 1.0 to 3.0 μm.

[0055] In these technical solutions, the performance indicators of aluminum hydroxide products are defined, including a sodium mass fraction not higher than 0.05%, whiteness ≥ 98%, and a particle size D50 of 1.0 to 3.0 μm. These performance indicators are important criteria for measuring the quality of aluminum hydroxide products. The control of the sodium mass fraction is to meet the requirements of high-end applications for product purity. A lower sodium mass fraction means fewer impurities in the product and more stable performance. Whiteness is an important indicator for measuring the appearance quality of the product. A higher whiteness means that the product is more in line with application requirements in appearance. The control of particle size D50 is to ensure the performance of the product in the application, such as dispersibility and filling performance in polymer composite materials. By defining the performance indicators of the product, it can be ensured that the prepared aluminum hydroxide product can meet the needs of high-end applications and has broad market application prospects. The mass fraction of sodium can be: 0.00%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05% and the like; the whiteness can be: 98%, 98.1%, 98.2%, 98.3%, 98.4%, 98.5%, 98.6%, 98.7%, 98.8%, 98.9%, 99.0% and the like; the particle size D50 can be: 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3.0 μm and the like.

[0056] The present application will be further described below in conjunction with specific examples. It should be understood that these examples are intended to illustrate the present application only and are not intended to limit the scope of the present application. The experimental methods in the following examples where specific conditions are not specified are generally measured according to industry standards. If there are no corresponding industry standards, then the methods are carried out according to general international standards, conventional conditions, or the conditions recommended by the manufacturer.

[0057] Example 1

[0058] Preparation of sodium aluminate solution:

[0059] Aluminum source material: high-purity industrial aluminum hydroxide (Al2O3≥99.8%); alkali solution: electronic grade NaOH solution (purity≥99.9%); dissolution temperature: 115°C; caustic ratio (αk): 1.52.

[0060] Add stabilizer: Stabilizer: organic phosphoric acid compound; Addition amount: 0.10wt%

[0061] Preparation of seed crystals: Seed crystal material: low sodium easy-to-grind aluminum hydroxide (Na2O content <0.1%); specific surface area: 12m 2 / g

[0062] Decomposition reaction: Decomposition temperature: 75°C; Seed addition amount: 5wt%; Decomposition time: 12 hours; Decomposition rate: 38%

[0063] Washing: solid-liquid ratio: 1:8; washing liquid conductivity: 0.5μS / cm;

[0064] Drying and crushing: Drying temperature: 80℃; Moisture content: 0.3%; Particle size: D50=1.5μm, D100<5μm

[0065] Example 2

[0066] Preparation of sodium aluminate solution: Aluminum source material: high-purity industrial aluminum hydroxide (Al2O3 ≥ 99.8%); alkali solution: electronic grade NaOH solution (purity ≥ 99.9%); dissolution temperature: 120°C; caustic ratio (αk): 1.56

[0067] Add stabilizer: stabilizer: polycarboxylic acid compound; addition amount: 0.08wt%;

[0068] Preparation of seed crystals: Seed crystal material: low sodium easy-to-grind aluminum hydroxide (Na2O content <0.1%); specific surface area: 10m 2 / g

[0069] Decomposition reaction: Decomposition temperature: 80°C; Seed addition amount: 6wt%; Decomposition time: 14 hours; Decomposition rate: 42%

[0070] Washing: solid-liquid ratio: 1:10; washing liquid conductivity: 0.8μS / cm

[0071] Drying and crushing: Drying temperature: 85°C; Moisture content: 0.4%; Particle size: D50 = 1.8 μm, D100 < 5 μm

[0072] Example 3

[0073] Preparation of sodium aluminate solution: Aluminum source material: high-purity industrial aluminum hydroxide (Al2O3 ≥ 99.8%); alkali solution: electronic grade NaOH solution (purity ≥ 99.9%); dissolution temperature: 110°C; caustic ratio (αk): 1.48

[0074] Add stabilizer: Stabilizer: inorganic salt compound; Addition amount: 0.05wt%;

[0075] Preparation of seed crystals: Seed crystal material: low sodium easy-to-grind aluminum hydroxide (Na2O content <0.1%); specific surface area: 11m 2 / g;

[0076] Decomposition reaction: Decomposition temperature: 65°C; Seed addition amount: 4wt%; Decomposition time: 10 hours; Decomposition rate: 30%

[0077] Washing: solid-liquid ratio: 1:7; washing liquid conductivity: 0.3μS / cm;

[0078] Drying and crushing: Drying temperature: 75°C; Moisture content: 0.2%; Particle size: D50 = 2.0 μm, D100 < 5 μm

[0079] Example 4

[0080] Preparation of sodium aluminate solution: Aluminum source material: high-purity industrial aluminum hydroxide (Al2O3 ≥ 99.8%); alkali solution: electronic-grade NaOH solution (purity ≥ 99.9%); dissolution temperature: 118°C; caustic ratio (αk): 1.54;

[0081] Add stabilizer: stabilizer: organic phosphoric acid compound; addition amount: 0.12wt%;

[0082] Preparation of seed crystals: Seed crystal material: low sodium easy-to-grind aluminum hydroxide (Na2O content <0.1%); specific surface area: 13m 2 / g;

[0083] Decomposition reaction: decomposition temperature: 78°C; seed addition amount: 7wt%; decomposition time: 16 hours; decomposition rate: 45%;

[0084] Washing: solid-liquid ratio: 1:9; washing liquid conductivity: 0.6μS / cm;

[0085] Drying and crushing: Drying temperature: 90°C; Moisture content: 0.3%; Particle size: D50 = 1.6 μm, D100 < 5 μm

[0086] Example 5

[0087] Preparation of sodium aluminate solution: Aluminum source material: high-purity industrial aluminum hydroxide (Al2O3 ≥ 99.8%); alkali solution: electronic grade NaOH solution (purity ≥ 99.9%); dissolution temperature: 125°C; caustic ratio (αk): 1.60;

[0088] Add stabilizer: stabilizer: polycarboxylic acid compound; addition amount: 0.07wt%;

[0089] Preparation of seed crystals: Seed crystal material: low sodium easy-to-grind aluminum hydroxide (Na2O content <0.1%); specific surface area: 14m 2 / g;

[0090] Decomposition reaction: decomposition temperature: 85°C; seed addition amount: 8wt%; decomposition time: 18 hours; decomposition rate: 50%;

[0091] Washing: solid-liquid ratio: 1:10; washing liquid conductivity: 0.7μS / cm;

[0092] Drying and crushing: Drying temperature: 95°C; Moisture content: 0.2%; Particle size: D50 = 1.7 μm, D100 < 5 μm

[0093] Example 6

[0094] Preparation of sodium aluminate solution: Aluminum source material: high-purity industrial aluminum hydroxide (Al2O3 ≥ 99.8%); alkali solution: electronic grade NaOH solution (purity ≥ 99.9%); dissolution temperature: 112°C; caustic ratio (αk): 1.50

[0095] Add stabilizer: Stabilizer: Inorganic salt compound; Addition amount: 0.06wt%

[0096] Preparation of seed crystals: Seed crystal material: low sodium easy-to-grind aluminum hydroxide (Na2O content <0.1%); specific surface area: 11m 2 / g;

[0097] Decomposition reaction: Decomposition temperature: 72°C; Seed addition amount: 5wt%; Decomposition time: 12 hours; Decomposition rate: 35%

[0098] Washing: solid-liquid ratio: 1:8; washing liquid conductivity: 0.4μS / cm;

[0099] Drying and crushing: Drying temperature: 80°C; Moisture content: 0.3%; Particle size: D50 = 1.9 μm, D100 < 5 μm

[0100] Comparative Example 1

[0101] Preparation of sodium aluminate solution: Aluminum source material: high-purity industrial aluminum hydroxide (Al2O3 ≥ 99.8%); alkali solution: electronic grade NaOH solution (purity ≥ 99.9%); dissolution temperature: 115°C; caustic ratio (αk): 1.25 (lower than the claim range)

[0102] Add stabilizer: stabilizer: organic phosphoric acid compound; addition amount: 0.10wt%;

[0103] Preparation of seed crystals: Seed crystal material: low sodium easy-to-grind aluminum hydroxide (Na2O content <0.1%); specific surface area: 12m 2 / g;

[0104] Decomposition reaction: Decomposition temperature: 75°C; Seed addition amount: 5wt%; Decomposition time: 12 hours; Decomposition rate: 28% (lower than the claim range)

[0105] Washing: solid-liquid ratio: 1:8; washing liquid conductivity: 0.5μS / cm;

[0106] Drying and crushing: Drying temperature: 80°C; Moisture content: 0.3%; Particle size: D50 = 2.5 μm, D100 < 5 μm

[0107] Comparative Example 2

[0108] Preparation of sodium aluminate solution: Aluminum source material: high-purity industrial aluminum hydroxide (Al2O3 ≥ 99.8%); alkali solution: electronic grade NaOH solution (purity ≥ 99.9%); dissolution temperature: 115°C; caustic ratio (αk): 1.75 (higher than the claimed range)

[0109] Add stabilizer: Stabilizer: polycarboxylic acid compound; Addition amount: 0.08wt%

[0110] Preparation of seed crystals: Seed crystal material: low sodium easy-to-grind aluminum hydroxide (Na2O content <0.1%); specific surface area: 10m 2 / g;

[0111] Decomposition reaction: Decomposition temperature: 80°C; Seed addition amount: 6wt%; Decomposition time: 14 hours; Decomposition rate: 42%

[0112] Washing: solid-liquid ratio: 1:10; washing liquid conductivity: 0.8μS / cm;

[0113] Drying and crushing: Drying temperature: 85°C; Moisture content: 0.4%; Particle size: D50 = 2.2 μm, D100 < 5 μm

[0114] Comparative Example 3

[0115] Preparation of sodium aluminate solution: Aluminum source material: high-purity industrial aluminum hydroxide (Al2O3 ≥ 99.8%); alkali solution: electronic grade NaOH solution (purity ≥ 99.9%); dissolution temperature: 110°C; caustic ratio (αk): 1.52

[0116] Add stabilizer: Stabilizer: Inorganic salt compound; Addition amount: 0.05wt%

[0117] Preparation of seed crystals: Seed crystal material: low sodium easy-to-grind aluminum hydroxide (Na2O content <0.1%); specific surface area: 11m 2 / g;

[0118] Decomposition reaction: decomposition temperature: 50°C (lower than the claimed range); seed crystal addition amount: 4 wt%; decomposition time: 10 hours; decomposition rate: 25% (lower than the claimed range);

[0119] Washing: Solid-liquid ratio: 1:5 (lower than the claimed range); Washing liquid conductivity: 1.0μS / cm (higher than the claimed range)

[0120] Drying and crushing: Drying temperature: 60°C; Moisture content: 0.5% (higher than the claimed range); Particle size: D50 = 3.0 μm (higher than the claimed range)

[0121] Effect data: The effect data of Examples 1 to 6 and Comparative Examples 1 to 3 are shown in Table 1.

[0122] Experimental methods for effect data:

[0123] 1. Determination of sodium mass fraction (Na2O): X-ray fluorescence spectrometry (XRF) is used to determine the sodium mass fraction in aluminum hydroxide products.

[0124] The samples were ground to a particle size of less than 0.075 mm.

[0125] Press the sample into a sheet, ensuring a flat surface.

[0126] XRF instrument was used for analysis to record the sodium content.

[0127] 2. Determination of whiteness: Use a blue light whiteness meter to measure the whiteness of aluminum hydroxide.

[0128] Spread the sample evenly on the sample stage.

[0129] Use a blue light whiteness meter to measure and record the whiteness value.

[0130] 3. Determination of particle size (D50): The particle size distribution of aluminum hydroxide was determined using a laser particle size analyzer.

[0131] The samples were dispersed in deionized water and sonicated for 10 min.

[0132] Use a laser particle size analyzer to measure, record the particle size distribution data, and calculate the D50 value.

[0133] Table 1

[0134]

[0135]

[0136] The above effect data table can intuitively compare the differences between different examples and comparative examples. The following conclusions can be drawn:

[0137] The aluminum hydroxide products prepared in Examples 1 to 6 all had a sodium mass fraction (Na2O) less than 0.05%, a whiteness greater than 98.5%, and a particle size (D50) between 1.5 and 2.0 μm, meeting the requirements of ultra-low sodium, high whiteness, and ultra-fine particle size. This demonstrates that the parameter range defined by the present invention can effectively control product quality and achieve the preparation of high-performance aluminum hydroxide.

[0138] In contrast, Comparative Example 1, due to its too low caustic ratio (1.25), has a sodium mass fraction of 0.10%, a whiteness of only 97.5%, and a particle size of 2.5 μm, failing to meet the requirements for ultra-low sodium and high whiteness. Comparative Example 2, due to its too high caustic ratio (1.75), has a sodium mass fraction of 0.08%, a whiteness of 98.0%, and a particle size of 2.2 μm. Although close to the requirements, it still does not meet the standards. Comparative Example 3 has an excessively low decomposition temperature (50°C), an excessively low solid-liquid ratio (1:5), and an excessively high detergent conductivity (1.0 μS / cm). Its sodium mass fraction is as high as 0.12%, its whiteness is only 96.0%, and its particle size is 3.0 μm. All indicators do not meet the standards. These comparative examples all fail to comply with the parameter ranges specified in the claims, resulting in substandard product quality.

[0139] The foregoing is merely a list of specific embodiments of the present application, intended to enable those skilled in the art to understand or implement the present application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application is not limited to the embodiments shown herein, but is intended to conform to the broadest scope consistent with the principles and novel features of the present application.

Claims

1. A method for preparing aluminum hydroxide, comprising: dissolving the aluminum source material with alkali solution to form a sodium aluminate solution; The caustic ratio of the sodium aluminate solution is 1.30 to 1.70; adding a stabilizer to the sodium aluminate solution; contacting the sodium aluminate solution containing a stabilizer with seed crystals having decomposition-inducing activity to carry out a decomposition reaction to obtain a decomposition product; The decomposition product is washed, dried and crushed in sequence to obtain an aluminum hydroxide product.

2. The preparation method according to claim 1, characterized in that The aluminum source material includes at least one of the following: aluminum hydroxide, aluminum oxide or a hydrate thereof.

3. The preparation method according to claim 1, characterized in that The alkali solution includes at least one of the following: sodium hydroxide solution and potassium hydroxide solution, and the purity of the alkali solution is ≥98%.

4. The preparation method according to claim 1, characterized in that The caustic ratio of the sodium aluminate solution is 1.40 to 1.

60.

5. The preparation method according to claim 1, characterized in that The stabilizer comprises at least one of the following: an organic phosphoric acid compound, a polycarboxylic acid compound, and an inorganic salt compound. The mass of the stabilizer is 0.05-0.15% of the mass of the sodium aluminate solution.

6. The preparation method according to claim 1, characterized in that The specific surface area of ​​the seed crystal is not less than 10m 2 / g, and the sodium mass fraction of the seed crystal is not higher than 0.2%.

7. The preparation method according to claim 1, characterized in that The parameters of the decomposition reaction include: a temperature of 50 to 90° C., a time of 10 to 24 hours, and a decomposition rate of the sodium aluminate solution of not less than 30%.

8. The preparation method according to claim 1, characterized in that The washing adopts a multi-stage countercurrent washing process, the conductivity of the washing liquid is not higher than 10 μS / cm, and the solid-liquid ratio of the washing is 1:5 to 1:

10.

9. The preparation method according to claim 1, characterized in that The drying temperature is 60-100° C., and the moisture content of the decomposition product after drying is not higher than 0.5%.

10. The preparation method according to claim 1, characterized in that The properties of the aluminum hydroxide product include at least one of the following: a sodium mass fraction not higher than 0.05%, a whiteness ≥ 98%, and a particle size D50 of 1.0 to 3.0 μm.

Citation Information

Patent Citations

  • Preparation method of high-purity ultra-fine aluminum hydroxide powder

    CN104724740A

  • Preparation method of high-dispersion superfine aluminium hydroxide

    CN105271336A

  • Method for preparing high-purity aluminium oxide

    CN107500324A

  • Fine particle-shaped aluminum hydroxide and its production

    JP1998130017A